Structures of the DfsB protein family suggest a cationic, helical sibling-lethal factor peptide - Taylor,J; Taylor,G; Hare,S; Matthews,SJ (Journal of Molecular Biology, 2016)
Bacteria have developed a variety of mechanisms for survivingharsh environmental conditions, nutrient stress and overpopulation.Paenibacillus dendritiformis produces a lethal protein (Slf) that is ableto induce cell death in neighboring colonies and a phenotypic switch inmore distant ones. Slf is derived from the secreted precursor protein,DfsB, after proteolytic processing. Here, we present new crystalstructures of DfsB homologues from a variety of bacterial species and asurprising version present in the yeast Saccharomyces cerevisiae.Adopting a four-helix bundle decorated with a further three short heliceswithin intervening loops, DfsB belongs to a non-enzymatic class of theDinB fold. The structure suggests that the biologically-active Slffragment may possess a C-terminal helix rich in basic and aromaticresidues that suggest a functional mechanism akin to that for cationicantimicrobial peptides.